Anti-obesity effects by parasitic nematode (Trichinella spiralis) total lysates - Kang, Shin Ae; Yu, Hak Sun (Frontiers in Cellular and Infection Microbiology, 2024)
Background Obesity is an inducible factor for the cause of chronic diseases and is described by an increase in the size and number of adipocytes that differentiate from precursor cells (preadipocytes). Parasitic helminths are the strongest natural trigger of type 2 immune system, and several studies have showed that helminth infections are inversely correlated with metabolic syndromes. Methodology/Principal findings To investigate whether helminth-derived molecules have therapeutic effects on high-fat diet (HFD)-induced obesity, we isolated total lysates from Trichinella spiralis muscle larvae. We then checked the anti-obesity effect after intraperitoneal administration and intraoral administration of total lysate from T. spiralis muscle larvae in a diet-induced obesity model. T. spiralis total lysates protect against obesity by inhibiting the proinflammatory response and/or enhancing M2 macrophages. In addition, we determined the effects of total lysates from T. spiralis muscle larvae on anti-obesity activities in 3T3-L1 preadipocytes by investigating the expression levels of key adipogenic regulators, including peroxisome proliferator-activated receptor gamma (PPARγ), CCAAT-enhancer-binding protein alpha (C/EBPα) and adipocyte protein 2 (aP2). Oil Red O staining showed that the total lysates from T. spiralis muscle larvae decreased the differentiation of 3T3-L1 preadipocytes by decreasing the number of lipid droplets. In addition, the production levels of proinflammatory cytokines IL-1β, IL-6, IFN-γ and TNF-α were examined by enzyme-linked immunosorbent assay (ELISA). T. spiralis total lysates decreased intracellular lipid accumulation and suppressed the expression levels of PPARγ, C/EBPα and aP2. Conclusion/Significance These results show that T. spiralis total lysate significantly suppresses the symptoms of obesity in a diet- induced obesity model and 3T3-L1 cell differentiation and suggest that it has potential for novel anti-obesity therapeutics.